Development of Curah Jero Nature Tourism in Attracting the Attention of Local and Foreign Tourists by KKN UMD 14 University of Jember - Ibnu Akbar Wicaksana; Igor Badar Rianof; Nuridalila; Muhammad Irsyaadil Lubab; Stevanus Faraldi Febriansyah; Raihan Nabil Pratama; Muhammad Zulkifly; Mashuri (Jurnal Pengabdian Pancasila (JPP), 2024)
Sidomulyo Village in Pronojiwo District, Lumajang, has tourism potential that has not been optimized, especially in the Curah Jero Nature Tourism with a rainbow mist waterfall. Despite offering spectacular views, the lack of infrastructure and promotions has hampered its appeal to tourists. In the UMD 14 UNEJ KKN research in January-February 2024, the focus was on improving infrastructure and marketing. Through discussions with local residents, tourism surveys, and the development of unique logos, the results show that infrastructure improvements and online marketing with distinctive logos can increase visits and the local economy. This research provides guidance for tourism managers and local governments to optimize Sidomulyo Village as a sustainable tourist destination, and can encourage economic growth and tourism sustainability in the region.